Rancang Bangun Aplikasi Monitoring Kebutuhan Masyarakat Untuk Relawan TIK Berbasis Web dan Mobile - Fitriani, Leni; Alfarisi, Muhammad Tsalman (Jurnal Algoritma, 2025)
Information and Communication Technology (ICT) volunteers face significant challenges in recording community needs because the process is still carried out manually and unstructured. This approach results in collected data often being scattered, difficult to analyze systematically, and ultimately hindering the effectiveness and speed of coordination in distributing aid. To overcome these problems, this study aims to design and build an integrated web- and mobile-based community needs monitoring system. This system was developed using the Rapid Application Development (RAD) method, which enables a fast and iterative development process. The mobile application serves as a tool for volunteers in the field to report needs in real time, while the web platform is used by managers for validation, assignment, and monitoring. Key features such as data visualization through heat maps, forms with automatic GPS, and photo uploads are integrated to improve data accuracy. Beta testing using the System Usability Scale (SUS) approach resulted in an average score of 76.25, which falls into the “Good” (Grade B) category. These results show that the system, built using Next.js, React Native, and PostgreSQL, has a high level of stability and has the potential to become a strategic tool for improving data collection efficiency and optimizing the distribution of social assistance digitally.